Identification and characterization of corn plants for downy mildew resistance in North Sumatra, Indonesia - DIANA SOFIA HANAFIAH; SYAMSAFITRI SYAMSAFITRI; MARIATI MARIATI; CHAIRANI HANUM; MUHDI MUHDI; GALI RAKASIWI; M. HAFAZH ABDURRAHMAN; M. AMIN NUR; DINA SAHTIKA (Society for Indonesian Biodiversity, 2025)
Abstract. Hanafiah DS, Syamsafitri, Mariati, Hanum C, Muhdi, Rakasiwi G, Abdurrahman MH, Nur MA, Sahtika D. 2025. Identification and characterization of corn plants for downy mildew resistance in North Sumatra, Indonesia. Biodiversitas 26: 2130-2138. The collection of germplasm determines the success of variety assembly. The genetic material contained in the germplasm has a strategic meaning in the assembly or improvement of varieties. This study aims to identify the kinship between morphological characteristics of individual corn plants. This study was conducted in Karo and Dairi Districts, North Sumatra, Indonesia from July-August 2024. Identification and plant characterization are carried out to preserve germplasm, which is the initial stage in breeding activities, especially in local germplasm. Characterization was carried out on corn genotypes in several villages in two districts in North Sumatra. The survey method used plant descriptors from the International Union for the Protection of New Varieties (UPOV) guide with a purposive method for determining the location and sampling technique. A total of 26 corn plant cultivars were studied. The result showed that based on the cluster method (grouping) of morphological characteristics, 3 groups were formed. The differences include stem color, leaf angle and ear tip shape. The closest cultivars are cultivars 14 and 16 from Kuta Tengah Village, Siempat Nempu Hulu Sub-district. The results of the characterization and identification of corn plants did not find any downy mildew attacks in Karo and Dairi Districts. The implication of this research is information on the diversity of corn germplasm and for the next stage the utilization of germplasm for corn plant breeding programs in North Sumatra.